Determinants of Workplace Accidents among Oil Palm Plantation Workers at PTPN IV Gunung Bayu, Simalungun, Indonesia - Pahala Maringan J Simangunsong; Rapael Ginting; Dameria Dameria; Santosa Nababan; Mey Lani Hutasoit; Risa Naftalia (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2026)
The palm oil industry in Indonesia operates under high occupational risk conditions, making occupational safety and health (OSH) a critical factor for ensuring both sustainability and productivity. This study aimed to identify factors significantly associated with workplace accidents among palm oil processing workers at PTPN IV Gunung Bayu, Simalungun. A descriptive, quantitative, cross-sectional design was employed, involving all 75 employees. Data were collected using questionnaires that assessed occupational accidents along with 6 independent variables: physical work environment, social work environment, use of personal protective equipment (PPE), machinery safety, work behavior, and participation in OSH training. These data were complemented by company accident reports from 2021 to 2024. Although workers reported generally positive perceptions of safety factors, 66.7% had experienced workplace accidents. Statistical analyses revealed significant associations between accidents and the physical work environment, PPE use, machinery safety, work behavior, and OSH training. Multivariate analysis identified the lack of OSH training as the most influential factor, increasing the risk of accidents by 5.1 times. These findings suggest that OSH training, specifically focusing on hazard awareness and safe work practices, is crucial for reducing workplace accidents. Key implementation challenges include engaging a diverse and experienced workforce. The study concludes that structured and periodic OSH training is vital for fostering a proactive safety culture and improving operational efficiency in the palm oil industry.